2015
DOI: 10.1111/conl.12184
|View full text |Cite
|
Sign up to set email alerts
|

Setting the Record Straight: Assessing the Reliability of Retrospective Accounts of Change

Abstract: Ecological degradation is accelerating, reducing our ability to detect and reverse declines. Resource user accounts have the potential to provide critical information on past change but their reliability can rarely be tested, hence they are often perceived as less valid than other forms of scientific data. We compared individual fishers' catch records, recorded 1-50 years ago, with their memories of past good, typical and poor catches for the corresponding time period. Good and poor catches were recalled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 34 publications
3
43
1
Order By: Relevance
“…Overall, this lends credibility to both modern and historical size estimates by participants in this study and beyond. This finding aligns with other studies that have used ecological research to corroborate traditional ecological knowledge or local ecological knowledge (Aswani & Hamilton, 2004;Johannes, 1998Johannes, , 2000Mallory et al, 2001;Poizat & Baran, 1997), or those that have found concurrence between scientific data and fishers' knowledge (Thurstan et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, this lends credibility to both modern and historical size estimates by participants in this study and beyond. This finding aligns with other studies that have used ecological research to corroborate traditional ecological knowledge or local ecological knowledge (Aswani & Hamilton, 2004;Johannes, 1998Johannes, , 2000Mallory et al, 2001;Poizat & Baran, 1997), or those that have found concurrence between scientific data and fishers' knowledge (Thurstan et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…In the Philippines, TEK of participants near the island of Bohol similarly aided in tracking population declines (and extirpations) of finfish populations for which no ecological data existed, prompting researchers to emphasize the potential value of TEK for new monitoring methods(Lavides et al, 2009). In general, TEK and LEK have provided conservation and management information that bolsters or extends pre-existing data(Beaudreau & Levin, 2014;Espinoza-Tenorio, Wolff, Espejel, & Montaño-Moctezuma, 2013;Huntington, 2000;Thornton & Scheer, 2012;Thurstan et al, 2016) using a socially-inclusive approach. As is the case for all methodologies, the use of TEK and LEK face challenges.This study addresses some key hurdles recognized broadly in the relevant literaturesample size limitations, restrictions in temporal accuracy, and subjectivity associated with human observationwhich are discussed below.…”
mentioning
confidence: 99%
“…We are aware of only one empirical study that compared resource user memories of catch changes to their own catch logbooks from the past. This study found that good and poor catches were recalled with reasonable accuracy, and that recalled typical catches were overestimated but comparable to mean values (Thurstan et al 2016). Thus, while human memory is not perfect, it can help to identify the direction and magnitude of change in the temporal trajectories of fished species.…”
Section: Introductionmentioning
confidence: 71%
“…Given the lack of biological data about Dungeness crab in the study region, we interviewed First Nations fishers about their experiences and perceptions of change. While there is support in the literature for using interviews to reconstruct catches and abundance, human memory can be fallible, especially with increased time (Thurstan et al 2016), and thus we cannot quantify the accuracy of estimates derived from the interview data. Additionally, we did not interview commercial and recreational fishers, and their observations can also help address scientific data gaps (Beaudreau and Levin 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There is some anecdotal evidence (personal communications with K. E. L. Simmons who was living on the island at that time) identifying the early 1960s as being when the decline in the Sooty Tern population began. Historical (mostly non-quantitative) records are increasingly being used in an attempt to quantify historical animal population sizes (Bonebrake et al 2010;Thurstan et al 2016). For example, on St Paul's Rocks, another island in the tropical Atlantic Ocean, Luiz and Edwards (2011) used historical records to substantiate anecdotal accounts of the decline in the size of reef shark Carcharhinus spp.…”
Section: The Value Of Demographic Data From Different Sourcesmentioning
confidence: 99%